Antanas Milukas - lietuvių knygos istorikas - Raguotis, Bronius (Knygotyra, 2024)
Antanas Milukas (1871-1943) is a well-known personality in the U.S. Lithuanian community. He was very active in different areas from the end of the nineteenth century to the middle of the twentieth— for more than 50 years. A. Milukas was an editor of periodicals for American Lithuanians, as well as a journalist, an initiator, founder, and member of different associations and organizations, and an author and publisher of books. Along with others (J. Šliūpas, J. Žilinskas), he was a historian of American Lithuanians and their culture. The article deals with the importance of A. Milukas’ activities and writings on the history of the Lithuanian book. He started to collect, research, and propagate this history in 1896 when he announced and published a significant find. That was "Giesmė"—a text published in 1874, which is considered to be the first publication by U.S. Lithuanians. A. Milukas wrote about the first Lithuanian publishers, editors, and authors in the USA (M. Tvarauskas, A. Zaicas, J. Paukštis, D. Bačkauskas, J. Šliūpas, etc.). He presented new and important material about their lives and works. A. Milukas was very interested in 19th-century Lithuanian literature, books, and culture. In 1900, in the second volume of "Lietuviškas albumas" (Lithuanian Album), he published a survey of 19th-century Lithuanian literature in Lithuanian and English. This was the first history of Lithuanian literature and, to some extent, of the Lithuanian book in the English language. The historiographic works of A. Milukas have not lost their importance to this day.